2015
DOI: 10.5539/jas.v7n7p228
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fluted Pumpkin (Telfairia occidentalis) Improves Reproductive Indices in Male African Catfish (Clarias gariepinus) Broodstock

Abstract: The effect of dietary aqueous extract of fluted pumpkin (Telfairia occidentalis) leaf powder on growth and reproductive indices of male catfish, Clarias gariepinus bloodstocks was investigated. Fish fed experimental diets showed significantly improved reproductive indices over the control fish. Significantly higher (P < 0.05) gonadosomatic index was recorded for the fish fed diets of aqueous extract of T. occidentalis leaf powder compared to fish fed on control diet. These results revealed that supplement diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…These bioactive are potent antioxidants which are capable of enhancing the production of female and male reproductive hormones (Olusola et al, 2021). The result of the study agreed with Dada (2013) who reported that medicinal plants supplemented diets enhance reproductive indices in C. gariepinus compared with the control diet. However, the report of Dada and Ajilore (2009), Adeparusi et al (2010), Dada and Ogunduyile (2011) revealed that incorporation of medicinal plants as pro-fertility agent may improve reproductive performance of male and female C. gariepinus, this report aligns with the findings of this present study.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These bioactive are potent antioxidants which are capable of enhancing the production of female and male reproductive hormones (Olusola et al, 2021). The result of the study agreed with Dada (2013) who reported that medicinal plants supplemented diets enhance reproductive indices in C. gariepinus compared with the control diet. However, the report of Dada and Ajilore (2009), Adeparusi et al (2010), Dada and Ogunduyile (2011) revealed that incorporation of medicinal plants as pro-fertility agent may improve reproductive performance of male and female C. gariepinus, this report aligns with the findings of this present study.…”
Section: Discussionsupporting
confidence: 87%
“…Due to the increase in demand for fish, there has been an increase in the use of synthetic chemicals as pro-fertility agent leading to negative effects on animal health and consumers Hence, attention is now focus on the use of an alternative that is safe and ecofriendly. Medicinal plants have been used to enhance fertility in fishes and animals such as Telfairia occidentalis (Dada and Ejete-Iroh, 2015), Garcinia cambogia (Oluyemi et al, 2007), Sesamum indicum (Dada and Adeparusi, 2012), Kigelia africana (Adeparusi et al, 2010), and Tribulus terrestris (Yeganeh et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It was proved that the extract of Tetracarpidium conophorum seed increases the viability and sperm output of male albino rats and this suggests that the seed could be included in the formulation of male fertility drugs (Ikpeme et al, 2014). However, Dada and Aguda, (2015) reported that the Tetracarpidium conophorum seed powder has potential profertility properties in male Clarias gariepinus (African sharp tooth catfish) that could be exploited in fish production as a feed additive for the improved reproductive performance of male African catfish. All parts of Tetracarpidium conophorum have been used ethnomedically, including the stem bark, leaves, seeds and roots.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of therapeutic active agents could be the reason for the analgesic activity of T. occidentalis [10]. T. occidentalis leaves has been reported to possess pro-fertility potentials that could be harnessed in fish fingerling production by hatchery farmers [11] while Kuku., et al [12] reported that T. occidentalis seeds could positively affect metabolism of nutrient and the growth performance in animals. The medicinal benefits of T. occidentalis have been reported on hematological indices of starter broilers [13], concentration of hemoglobin and packed cell volume [14], lipid peroxidation amelioration and cardiovascular disease reduction [15].…”
Section: Introductionmentioning
confidence: 99%